Pomnik Walki i Męczeństwa Ziemi Bydgoskiej. Między pamięcią a propagandą (Kronika Bydgoska, 2010)
In the 1960’s, the authorities of Bydgoszcz city decided in a elear way to commemorate the city residents murdered by the German occupants in September 1939. To this end, the Voivodeship Civic Committee for Protection of Fighting and Martyrdom Monuments organised through the agency of the Polish Visual Artists’ Association the competition for a monument and surrounding development design. The competition was judged in December 1963 and the winner was Wacław Kowalik’s design depicting a figurę of the goddess Nike placed on a high column, with martyrdom bas-reliefs in its bottom part. Finally, this design was not implemented, and another, closed competition was announced in the autumn of 1966. Eight artists recognised in Poland and abroad were asked to make a design for a monument being “a symbol of martyrdom, fighting and victory of the Bydgoszcz community over the Nazi occupant”. The winners were Włodzimierz Padlewski with a design of a museum building and Franciszek Masiak with an idea of a multi-figure sculpture. This sculpture appeared in the Bydgoszcz Old Town Market Sąuare, unveiled on September 5, 1969 with accompanying official State ceremonies. The communist authorities used the monument for propaganda against the Federal Republic of Germany.